2-Mercaptoimidazole selectively etching and thiol-functionalized ZIF-8 metal–organic framework to serve as a multifaceted platform for radical scavenging and Au loading. (January 2023) - Chen, Y.-L.; Lee, G.-Y.; Tang, D.-W.; Huang, K.; Lo, P.-Y.; Huang, J.-H.; Cho, E.-C.; Lee, K.-C.
Abstract: Zeolite imidazole frameworks (ZIF-8) are a group of metal–organic frameworks (MOFs) that harbor application potential due to their unique high porosity and other physicochemical properties. However, the small cavities, unstable dispersion, and the lack of surface functional groups hinder the practical application of ZIF-8. In this study, we aimed to develop a ZIF-8-based multifaceted platform with hollow structure and abundant functional groups via a simple one-pot method. We synthesized the ZIF-8 with thiol functionalization (ZSH), while 2-mercaptoimidazole was served as both etching agent and functional counterpart. The hollow morphology and the thiol-groups modification were validated by scanning electron microscopy, transmission electron microscopy with energy-disperse X-ray mapping and X-ray photoelectron spectroscopy. The interparticle structure was estimated by Brunauer–Emmmett–Teller and ultraviolet–visible spectroscopy. The hollow architecture, colloidal stable, and thiol-abundant surface endow ZSHs exploiting the antioxidant and anti-inflammatory ability than pristine ZIF-8 toward a broad scale of morphological change with high functionalization degree. Moreover, ZSHs can specifically encapsulate gold nanoparticles in large quantities for further applications. Finally, ZSHs possess good biocompatibility in human cells and in vivo zebrafish model and could potentially protect human cells against oxidative stress. This concept valuably elucidated the new era for functionalized ZIF-8 to apply as the next generation of multifunctional biomaterials. Graphical abstract: ZSH synthesis with thiol selectively functionalized and etching reaction by 2-mercaptoimidazole. Image 1 Highlights: ZIF-8-based multifaceted platform with hollow structure and abundant functional groups via a simple one-pot method. ZIF-8 with thiol functionalization (ZSH), while 2-mercaptoimidazole was served as both etching agent and functional counterpart. The hollow architecture, colloidal stable, and thiol-abundant surface endow ZSHs exploiting the antioxidant and anti-inflammatory ability. ZSHs can specifically encapsulate gold nanoparticles in large quantities for further applications.